Improved Performance of Deep Ultraviolet Photodetector From Sputtered Ga2O3 Films Using Post-Thermal Treatments - Hui Li; Po-Wei Chen; Shuo-Huang Yuan; Tsun-Min Huang; Sam Zhang; Dong-Sing Wuu (IEEE Photonics Journal, 2019)
The metal-semiconductor-metal photodetectors based on the sputtered gallium oxide films on sapphire substrates after various post-thermal treatments have been investigated. The photodetector performance of the furnace-annealed gallium oxide sample degraded with the increase of annealing temperature from 700 to 1000 °C, resulting from the adverse effect of the aluminum cross-diffusion and polycrystalline formation. By rapid thermal annealing at 800 °C, the gallium oxide film can achieve an optimum photodetector performance with the photo/dark current ratio of 1.78 × 105 (@5V and 230 nm), responsivity of 0.553 A/W, and fast transient response (rise/fall time: 0.2 s/0.1 s). The result is comprehensively better than the previous reports by sputtering, which demonstrates that the quasi-single-crystalline gallium oxide film via rapid thermal process has high potential for deep-ultraviolet photodetector applications.